Microscopical advances: the posterity of Huygens´simple microscope of 1678 - Turner, Anthony (ENDOXA, 2004)
From an examnation of recently rediscovered examples of the simple microscope with spherical lens and specimen revolver, originally developed by Christiaan Huygens, the paper seeks to ¡Ilústrate how the combined study of texts and objects is essential to establishing the evolution of an instrument. Some of the newly discovered Instruments are described and comment ¡s made on the commercial forces w^hich acted in parallel with scientific ones on the development of this particular form of microscope